The Effects of Mindfulness-Based Training on Psychological Wellbeing and Emotion Regulation of Menopausal Women: A Quasi-experimental Study - Mohammad Sadegh Zamani Zarchi; Roghieh Nooripour; Ali Hosseinzadeh Oskooei; Gholam Ali Afrooz (Gonabad University of Medical Sciences, 2020)
Background: Menopause is one of the most critical phenomena in women's lives, leading to emotional and behavioral symptoms in many cases. In this regard, this study aimed to determine the effectiveness of mindfulness training for menopausal women on psychological wellbeing and emotional regulation. Methods: The research method, conducted in 2019, was quasi-experimental with a Pre-test-Post-test design and a control group. This study population included all menopausal women referring to Rasht City healthcare centers. A total of 28 women were selected using the convenience sampling method based on the study criteria and were randomly assigned to the experimental and control groups (n=14). Ryff's psychological wellbeing questionnaire (1989) and emotion regulation questionnaire (Gross and John, 2003) were asked to complete all participants. The experimental group received an 8-session mindfulness training and the control group did not receive any training program. Results: The results of multivariate analysis of covariance showed that the Mean±SD scores of psychological wellbeing 166.47±18.94 and emotional regulation 25.56±4.12 in the experimental group increased significantly in the Post-test (P<0.05), i.e., 188.67±12.220 for the psychological wellbeing and 37.02±5.12 for the emotion regulation. Conclusion: Mindfulness training is an effective way to improve menopausal women's psychological wellbeing and emotional regulation and it can be used to help these women by counselors and therapists.